Successes rate of endoscopic dacryocystorhinostomy at KMC - Shrestha, S; Kafle, PK; Pokhrel, S; Maharjan, M; Toran, KC (Kathmandu University Medical Journal, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Background: Nasolacrimal duct obstruction is a common problem which can be corrected by dacryocystorhinostomy (DCR). The gold standard treatment for this is DCR operation through an external approach. Development of endoscopic sinus surgery and endoscopic DCR performed through intranasal route is a major recent development in this field. Objectives: The aim of this study is to find out the success rate of endoscopic dacryocystorhinostomy without silicon stent intubation within the period of six month following surgery. Materials and methods: A prospective study was done on 26 patients with obstruction of the nasolacrimal duct referred from eye out-patient department to ENT OPD during one year period from 2008 to 2009. All the cases had undergone endoscopic DCR operation which was regularly followed up for a period of six months. Postoperative patency of ostium was checked by sac syringing and endoscopic visualisation of ostium in the nasal cavity. The success of surgery was categorised as: complete cure, partial cure and no improvement depending upon symptomatic relief and clinical examination such as sac syringing and endoscopic examination following surgery. Result: In six months' follow-up, 22 (84.5%) out of 26 patients had achieved the complete cure and 4 patients (15.5%) continued to have persistent epiphora. Conclusion: Endoscopic DCR is a beneficial procedure for nasolacrimal duct obstruction with no external scar on face and less bleeding. The success rate is as good as external DCR. Key words: Nasolacrimal duct; Epiphora; Rigid nasal endoscope; Endoscopic Dacryocystorhinostomy DOI: 10.3126/kumj.v8i2.3557 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 195-198